1992
DOI: 10.1021/ma00038a047
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of nonalternating poly(ester amides)

Abstract: Introduction.Aliphatic polyesters are an important class of biodegradable and hydrolyzable synthetic polymers.'" A series of a-hydroxypolyesters, such as poly-(glycolic acid) (PGA), poly(1actic acid) (PLA), and their copolymers, have been successfully used as bioabsorbable sutures and surgical implants.lt3 Other types of polyesters,415 such as poly(caprolactone), poly(@-propiolactone), and poly(butyrolactone), can also be potentially used as biodegradable polymers in drug delivery and agricultural uses.On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 3 publications
1
68
1
Order By: Relevance
“…In conclusion, the slight decrease of the number of fungi in the earthworms casts compared to the population found in biosynthesol shows that earthworms regulate the number of fungi mostly by eating them. Among those fungi, Fusarium and Aspergillus strains known as able to bioassimilate PLA (Fusarium, Torres et al, 1996c) or other aliphatic esters (Aspergillus, Nishida et Tokiwa, 1993, Gonsalves et al, 1992 were found. It is thus probable that OLA is first degraded by those fungi and also by bacteria, and then earthworms eat them.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the slight decrease of the number of fungi in the earthworms casts compared to the population found in biosynthesol shows that earthworms regulate the number of fungi mostly by eating them. Among those fungi, Fusarium and Aspergillus strains known as able to bioassimilate PLA (Fusarium, Torres et al, 1996c) or other aliphatic esters (Aspergillus, Nishida et Tokiwa, 1993, Gonsalves et al, 1992 were found. It is thus probable that OLA is first degraded by those fungi and also by bacteria, and then earthworms eat them.…”
Section: Resultsmentioning
confidence: 99%
“…However, polyester-amides composed of esters and amides could potentially have better physical and mechanical properties than polyester with retention of biodegradability characteristics of the polyesters. 4 -8 Synthesis of such materials via anionic copolymerization of -caprolactam with -caprolactone has been investigated by Goodman et al 9 -12 Gonsalves et al, 13 and Nakayama et al 14 Goodman et al 9 showed that, in anionic copolymerization studies using N-sodium caprolactam as a catalyst, at both high and low initial -caprolactam/-caprolactone feed ratio (70/30 or 25/ 75), incorporation of -caprolactam units into the copolymer increased at higher catalyst concentrations (1 and 2%) and with reaction time. For a catalyst level of 0.5%, at the same feed ratios, -caprolactone is the major component in copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Such PEAs can be prepared by condensing either (i) lactones with lactams or (ii) lactones and lactams with diamines, diols and diacid derivatives [1][2][3][4][5][6][7][8][9][10][11]. BAK ® 1095, a commercial product from Bayer is a random semi-crystalline PEA based on ε-caprolactam, 1,4-butanediol and adipic acid [1,2].…”
Section: Random Microstructurementioning
confidence: 99%
“…Ringopening co-polymerization of lactones and lactams affords random co-polymers [1,2,[4][5][6][7][8][9][10][11][104][105][106][107]. Aliphatic and/or aromatic dicarboxylic acids and diols with varying number of methylene groups give rise to various microstructures and architectures.…”
Section: Synthetic Monomers/building Blocksmentioning
confidence: 99%